DOP02 αEβ7 positive γδ T cells are associated with mucosal healing in Ulcerative Colitis and have a homeostatic immunophenotype. (27th May 2021) - Dart, R; Zlatareva, I; Irving, P; Hayday, A
Abstract: Background: α4β7 blockade is a well-established therapy in ulcerative colitis (UC), acting in part by preventing lymphocyte ingress into the mucosa. The β7 unit of the α4β7 heterodimer is shared by α Ε β7, which is expressed on both tissue resident memory cells and γδ intra-epithelial lymphocytes (IEL). It was hypothesised that targeting both α4- and α Ε β7 might be more efficacious; however mixed results from phase III studies of β7 blockade asks questions of the biological relevance of different α E β7 expressing cells. Methods: Colonic biopsies were obtained during endoscopy from >40 subjects. Lymphocytes were isolated using short term culture or digested from whole tissue. RNA sequencing was performed on α Ε β7 pos and α Ε β7 neg colonic γδ T cells from 4 donors and findings were validated by flow cytometry. Results: α Ε β7 is widely expressed on TCRαβ CD8 cells and γδ IEL in both non-IBD controls and the uninflamed mucosa in UC, but its expression is significantly reduced on analogous subsets harvested from inflamed UC. On further study, the capacity of TCRαβ CD8 T cells to make TNFα and IFNγ on stimulation is similar between α Ε β7 pos and α Ε β7 neg cells, whereas in the γδ T cell compartment α Ε β7 neg cells produce significantly more pro-inflammatory cytokine than their homeostatic α Ε β7 pos counterparts. To examine the cells' biology further, γδ T cells were isolated according to their α Ε β7 status and RNAseq undertaken. This revealed a distinct signature with α Ε β7 neg cells demonstrating an activated phenotype high in markers such as CD18, CD5 and lymphoid homing receptor CCR7 whereas α Ε β7 pos cells demonstrate a homeostatic tissue-resident phenotype, expressing immune checkpoints TIGIT and CD101 and gut-homing marker CCR9. On culturing tissue from non-IBD controls in pro-inflammatory cytokines, IL-12 and IL-18, the γδ T cell compartment down-regulated α Ε β7 and TIGIT and upregulated CD18, in part recapitulating a disease phenotype. On examining previously affected mucosa of patients who have achieved mucosal healing, α E β7 expression of the γδ T cells returned to a profile resembling non-IBD controls whereas the expression levels in the inflamed mucosa remained predictably low. Conclusion: This study demonstrates that α Ε β7 expression is low in active UC but restored in mucosal healing. α Ε β7 neg cells are proinflammatory with a distinct phenotype which may in part be recapitulated by inflammatory cytokines in vitro ; whereas α Ε β7 pos cells demonstrate a homeostatic phenotype, which may both reflect and maintain steady state barrier integrity. Hence in terms of γδ T cells, pharmacological β7 blockade has potential to interfere with the homeostatic roles of α Ε β7 expressing cells while having little effect on a potentially pathogenic subset of tissue α Ε β7 neg γδ cells.